PENGEMBANGAN KUIS INTERAKTIF BERBASIS WORDWALL UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SDN KREBET BANTUL - Istiqomah; Muhayat Wiji Wahyudi, Urip (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to produce an interactive quiz product by utilizing the WordWall platform in Pancasila Education learning to encourage increased learning motivation of students in grade IV of elementary school. This study uses the Research and Development (R&D) method with the ADDIE model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects involved in this study were 18 grade IV elementary school students. Data were collected using observation, questionnaires, interviews and documentation techniques. The instruments used in this study consisted of a media expert validation sheet, a material expert validation sheet, as well as a student response questionnaire, a teacher response questionnaire, and a learning motivation questionnaire. The collected data were analyzed using quantitative and qualitative descriptive approaches and paired sample t-tests. The results showed that the WordWall-based interactive quiz obtained a feasibility level of 91.1% based on the media expert assessment. Meanwhile, the assessment from the material expert obtained 95% which is classified as very feasible. Furthermore, the results of the student response questionnaire showed a percentage of 82.5%–100% and the results of the teacher's response were obtained at 100% with very practical criteria. In addition, the average level of student learning motivation showed a significant increase from the original 86.75% to 90.25%. The results of the paired sample t-test showed a Sig. (2-tailed) value of 0.023 < 0.05 which proved that the use of interactive quizzes based on WordWall has proven to have a positive impact on student learning motivation. Thus, interactive quizzes based on WordWall are declared suitable for use as interactive learning media in Pancasila Education learning at the elementary school level.